Analisis Kesesuaian Ruang Hijau pada Hutan Kota untuk Perencanaan Kota Berkelanjutan - Suciyani, Wida Oktavia; Hinanti, Arifha Nurhaliza (Jurnal Pembangunan Wilayah dan Kota, 2021)
The rise of development in a city causes the existence of green open spaces decrease. The development of green open spaces plays an important role in overcoming environmental problems in cities and supporting the realization of green cities in sustainable urban planning. The aim of this study is to determine the suitability of green space in the Babakan Siliwangi Urban Forest based on green space suitability criteria. The research method used is descriptive qualitative and quantitative with data collection techniques are observation, interviews and documentation studies. Based on the analysis result, it is known that the Babakan Siliwangi Urban Forest has not met the green space suitability criteria including accessibility, physical and socio-economic. Recommendations for further research are planning for the development of Babakan Siliwangi Urban Forest.